Rancang Bangun Sistem Informasi Website Company Profile pada Industri Perhotelan - Agus Priyadi; Andik Prakasa Hadi; Ahmad Zainudin; Ayrelliano Reyvanda Nugroho (LPPM Sekolah Tinggi Ilmu Ekonomi - Studi Ekonomi Modern, 2024)
This study aims to develop a web-based information system as a company profile for the hospitality industry, specifically for Hotel Griya Wijaya Ambarawa. The development method used is Research and Development (R&D), involving an iterative process to enhance the efficiency and effectiveness of the website. The results of this study indicate that the designed website not only improves hotel promotion but also expands market reach through interactive features such as an online reservation system and social media integration. The website is also designed to provide an optimal user experience with a responsive design, ultimately increasing reservations and customer satisfaction.